GAMBARAN SIKAP DAN PERILAKU ORANG TUA TERHADAP KEBUTUHAN GIZI USIA BALITA PASCA BENCANA H-1 DI SUMATERA BARAT - Welly Andria Mela Sari (Akper Kesdam I/Bukit Barisan Padang, 2019)
Nutrition is a factor that plays an important role in the growth and development of children under five. In the aspect of nutrition, the role of parents, especially mothers, is very important because it is the closest person to the child especially in a disaster situation the mother must be able to provide balanced nutritional needs for toddlers. This study aims to obtain an overview of the attitudes and behaviors of mothers in fulfilling the nutrition of toddlers post-disaster H-1. This survey involved mothers who had children aged 13 to 59 months in the Solok SelatanRegion of West Sumatra totaling 112 respondents. The sampling technique used was multistage random sampling and consecutive sampling. The survey results showed that 75.9% of mothers had sufficient knowledge, 57.1% of mothers had a good enough attitude, and 71.4% of mothers behaved well in fulfilling the nutrition of children under five. The results of this study indicate a positive condition and mothers are able to provide nutritional needs for toddlers even in disaster situations but need to be investigated more deeply so that the main problems related to toddler nutrition can be identified